Implementasi Project Based Learning Untuk Meningkatkan Aktivitas dan Keterampilan Menulis Siswa SMP Taman Dewasa Jetis - Ermawati Ermawati; Widowati Widowati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
This study aims to describe learning activities and writing skills through Project Based Learning. The subjects of this study were students of class VII-I Junior High School at Taman Dewasa Jetis. Classroom action research was conducted in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The source of data in this class action research is the process of learning description text and fantasy narrative texts and documents. Data collection is done through observation techniques, documentation (field notes, student lists, student grades, lesson plans, student test results, and photographs), and tests. Data analysis techniques using the Miles and Huberman techniques. The application of Project Based Learning procedures includes: asking questions; make a plan; arrange scheduling; monitor project creation; conduct an assessment; and evaluation. The results of student activities in learning have increased, as well as writing skills also showed an increase.